Does Scientific Progress Affect Culture? A Digital Text Analysis - Michela Giorcelli; Nicola Lacetera; Astrid Marinoni (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the interplay between scientific progress and culture through text analysis on a corpus of about eight million books, with the use of techniques and algorithms from machine learning. We focus on a specific scientific breakthrough, the theory of evolution through natural selection by Charles Darwin, and examine the diffusion of certain key concepts that characterized this theory in the broader cultural discourse and social imaginary. We find that some concepts in Darwin's theory, such as Evolution, Survival, Natural Selection and Competition diffused in the cultural discourse immediately after the publication of On the Origins of Species. Other concepts such as Selection and Adaptation were already present in the cultural dialogue. Moreover, we document semantic changes for most of these concepts over time. Our findings thus show a complex relation between two key factors of long-term economic growth – science and culture. Considering the evolution of these two factors jointly can offer new insights to the study of the determinants of economic development, and machine learning is a promising tool to explore these relationships.
Keywords: C19; C89; N00; O00; O39; Z19; 330; science; culture; economic history; text analysis; machine learning